The Van Allen Probes Mission - Fox, Nicola.; Fox, Nicola.; Burch, James L.; Burch, James L. (Springer US : Imprint: Springer, 2014)
This collection of articles provides broad and detailed information about NASA’s Van Allen Probes (formerly known as the Radiation Belt Storm Probes) twin-spacecraft Earth-orbiting mission. The mission has the objective of achieving predictive understanding of the dynamic, intense, energetic, dangerous, and presently unpredictable belts of energetic particles that are magnetically trapped in Earth’s space environment above the atmosphere. It documents the science of the radiation belts and the societal benefits of achieving predictive understanding. Detailed information is provided about the Van Allen Probes mission design, the spacecraft, the science investigations, and the onboard instrumentation that must all work together to make unprecedented measurements within a most unforgiving environment, the core of Earth’s most intense radiation regions. This volume is aimed at graduate students and researchers active in space science, solar-terrestrial interactions and studies of the upper atmosphere. Originally published in Space Science Reviews, Vol. 179/1-4, 2013.